Development and validation of a new spectrophotometric method for simultaneous determination of sitagliptin and metformin hydrochloride in tablet pharmaceutical dosage forms using chemometrics technique in comparison with HPLC - Ali Almaqtari, Maher; Al-Odaini , Najat Ahmed; Alarbagi , Fares Abdullah; Al-Maydama, Hussein (Eclética Química, 2023)
A new, quick, easy, affordable and eco-friendly simultaneous spectrophotometric method for determining a combined sitagliptin and metformin hydrochloride in pharmaceutical formulations was developed and validated using two chemometrics technique. These two methods are the partial least square (PLS) and principal component regression (PCR). They do not need to do a sample preparation or separation before analysis. Various drug concentrations and instrumental spectra of 25 mixed solutions of a combination of sitagliptin and metformin hydrochloride were used for model construction in the range of 200–270 nm. The R2 values of 0.9994 and 0.9996 assigned for the PLS of the sitagliptin and metformin hydrochloride and that of 0.9987 and 0.9996 for the PCR of the sitagliptin and metformin hydrochloride, respectively. It is noteworthy that these two models were successfully and effectively used with the commercial pharmaceutical formulations. Finally, the statistical comparison revealed no significant differences with the results of the HPLC reference method. The proposed method is dependable to be adopted as an alternative analytical method in the pharmaceutical industry’s quality control.